VIRTUAL ETHNOGRAPHY OF THE CULTURE AND BEHAVIOR OF THE CIBALIUNG COMMUNITY IN UTILIZING FACEBOOK PRO AS A SPACE FOR EXPRESSION AND A SOURCE OF ECONOMIC OPPORTUNITIES - David Hermawan; Aulia Rahmawati (Adisam Publisher, 2026)
The rapid advancement of digital technology has transformed the function of social media from merely a communication platform into a space for self-expression and a new source of economic opportunities for society, including rural communities. This study aims to gain an in-depth understanding of how culture and behavior are constructed within the Cibaliung Community, a public Facebook group with approximately 46.5 thousand members, in utilizing the Facebook Pro feature as a space for expression and a source of economic opportunities. The study employed a qualitative approach using a virtual ethnography method based on Christine Hine's framework, supported by Henry Jenkins' theory of Participatory Culture and the concept of Digital Empowerment. Data were collected through participant observation and digital documentation of posts, comments, and interactions among community members over a period of approximately three months. The data were then analyzed using the Miles and Huberman interactive analysis model, while the trustworthiness of the findings was established through source, technique, and time triangulation. The findings indicate that Facebook Pro is utilized as a space for personal expression, religious expression, local Sundanese-language humor, and digital creativity; as a source of economic opportunities through content monetization, product promotion and sales, and access to employment information; and as a discussion forum in which the comment section has evolved into a collective deliberative space for addressing both local and national issues. These findings demonstrate that the boundary between online and offline spaces has become increasingly blurred and illustrate how rural communities are capable of achieving digital empowerment without requiring substantial capital investment.